1990
DOI: 10.1093/oxfordjournals.jbchem.a123256
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization and Preliminary X-Ray Diffraction Studies of C-Phycocyanin from a Red Alga, Porphyra tenera1

Abstract: C-Phycocyanin from a red alga, Porphyra tenera, has been crystallized by the vapor-diffusion procedure. Both orthorhombic and hexagonal forms were obtained from ammonium sulfate solutions, whereas only the orthohombic form was selectively grown from sodium citrate solutions. The orthorhombic crystals are more suitable for further crystallographic work; their space group is P2(1)2(1)2(1), with unit-cell dimensions of a = 105, b = 121, and c = 184 A. The asymmetric unit comprises two (alpha beta)3 trimer molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The three-dimensional structures of C-PC from Mastigocladus laminosus (Schirmer, Bode, Huber, Sidler & Zuber, 1985;Schirmer, Bode & Huber, 1987;Duerring, Huber & Bode, 1988), Agmenellum quadruplicatum (Schirmer et al, 1986(Schirmer et al, , 1987 and Fremyella diplosiphon (Duerring, Schmidt & Huber, 1991) were determined by highresolution X-ray crystallography. Crystallization and preliminary X-ray diffraction studies of C-PC from the red alga Porphyra tenera were also reported (Miki et al, 1990). However, C-PC from S. platensis has been neither crystallized or X-ray characterized.…”
Section: Introductionmentioning
confidence: 99%
“…The three-dimensional structures of C-PC from Mastigocladus laminosus (Schirmer, Bode, Huber, Sidler & Zuber, 1985;Schirmer, Bode & Huber, 1987;Duerring, Huber & Bode, 1988), Agmenellum quadruplicatum (Schirmer et al, 1986(Schirmer et al, , 1987 and Fremyella diplosiphon (Duerring, Schmidt & Huber, 1991) were determined by highresolution X-ray crystallography. Crystallization and preliminary X-ray diffraction studies of C-PC from the red alga Porphyra tenera were also reported (Miki et al, 1990). However, C-PC from S. platensis has been neither crystallized or X-ray characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent accurate X-ray structural studies of C-PC from a variety of organisms were reported. In general, almost all these studies have shown that the overall sequences of the C-PC complexes are very similar, albeit slight differences in their biophysical and biochemical properties [ 28 30 , 32 45 ].…”
Section: Introductionmentioning
confidence: 99%